Stock price and Foreign Exchange Rate in Malaysian Context - Thinagar, Sharmila (School of Social Sciences, 2015)
This study investigates the correlation and causality direction between FTSE Bursa Malaysia Kuala Lumpur Composite Index and five foreign exchange rates namely United States Dollar (USD), Great Britain Pounds (GBP), Euro Dollar (EURO), Singapore Dollar (SGD) and Thailand Bhat (THAI) using a standard time series method. Using a monthly data spanning from January 1994 until December 2014. The empirical findings shows that the stock return granger cause the return of exchange rate. Thus, it can be concluded that there is a unidirectional causality between stock market and exchange rate and it is supportive of “portfolio balances” model. This study implied that the stability of the exchange rate is defend on the stability of the stock price, and therefore the policy makers need to observe precisely the movement of stock market and exchange rate.